Strategic Health Planning and Data-Driven Stunting Reduction in Sumedang Regency - Nanang Suparman (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Stunting reduction requires not only nutrition programmes but also strategic health service planning supported by reliable local data. This study aims to analyse how stunting data are used in strategic health service planning to support stunting reduction in Sumedang Regency. The study is informed by Strategic Planning, Evidence-Based Decision Making, and Collaborative Governance, which explain the links between data, priority setting, institutional coordination, and service control. A qualitative descriptive case study was employed using documentary analysis of government reports, health office data, child weighing records, BPS publications, regulatory documents, the SIMPATI platform, open datasets, and previous studies published no later than 30 March 2025. The findings show that stunting data in Sumedang support problem mapping, territorial priority setting, service coordination, and intervention monitoring. However, the strategic value of data depends on input quality, user capacity, inter-agency integration, and consistent follow-up across priority areas for more adaptive local health service decisions.